Scenario in Managing Employee Performance at PT XYZ - Nofal Alfiansyah; M. Syamsul Maarif; Elisa Anggraeni (Business Review and Case Studies, 2023)
Employee performance improvement is very essential for company organization because it could improve the company's existence in the market competition and also expand their business innovation. However, to improve the employee's performance, there are several factors and variables that could affect it. Therefore, this research aimed to analyze the effect of those variables, which are knowledge management, affective commitment, organization culture, and employee motivation. Furthermore, to analyze those variables, this research used a quantitative method and questionnaire with 52 respondents in the PT XYZ operational area. The data will be processed using SEM PLS analysis, and the result shows that knowledge management, affective commitment, and employee culture have a significant impact on employee performance. The only variable that does not have a significant effect is organizational culture, but it could indirectly affect employee performance through the motivation variable. There are two scenario plans created using the TAIDA approach. Scenario 1 is conducting extensive training for all employees based on the needs of the division in which they operate. Scenario 2 training and education is only available for employees with high potential for cost efficiency. Keywords: commitment affective, employee motivation, employee performance, knowledge management, organization culture